Periventricular white matter lesion and incomplete MRZ reaction in a male patient with anti-N-methyl-d-aspartate receptor encephalitis presenting with dysphoric mania. (26th April 2015) - Gahr, Maximilian; Lauda, Florian; Wigand, Moritz E; Connemann, Bernhard J; Rosenbohm, Angela; Tumani, Hayrettin; Reindl, Markus; Uzelac, Zeljko; Lewerenz, Jan
Abstract : Several findings suggest that there may be an overlap of anti- N -methyl-d -aspartate receptor (NMDAR) antibody encephalitis with neuromyelitis optica spectrum disorders or acute demyelinating encephalomyelitis (ADEM)-like demyelination. We present a case of a patient with anti-NMDAR antibody encephalitis, who on MRI featured a single prominent T2-hyperintensive white matter lesion in the periventricular region, adjacent to the anterior horn of the left lateral ventricle. In view of the lesion location and the cerebrospinal fluid (CSF) findings (incomplete MRZ (measles, rubella and varicella zoster) reaction, lymphocytic pleocytosis, intrathecal IgG and IgM synthesis; absence of aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG) antibodies), the presence of a multiple sclerosis-like immune response was discussed. This case appears to add evidence to the hypothesis of an overlap between anti-NMDAR antibody encephalitis and other inflammatory central nervous system diseases.